The Influence of Brand Ambassador and Brand Image on Purchase Intention of Wardah Products (A Study on Students of Business Management Study Program, Politeknik Negeri Kupang) - Baunsele, Petrus; Jaiman, Lili (CV. Jala Berkat Abadi, 2025)
This study investigates the purchase intention of students from the Business Management Study Program at Politeknik Negeri Kupang toward Wardah products and examines the influence of brand ambassador and brand image. The research is motivated by the growing competition in Indonesia’s cosmetics industry. Wardah, a local halal cosmetic brand, employs marketing strategies such as brand ambassadors and a strong brand image to attract customers, particularly the younger generation. Using an explanatory quantitative approach, this study employed multiple linear regression and distributed questionnaires to 55 respondents. The data were analyzed using t-test, F-test, and the coefficient of determination (R²). The findings reveal that both brand ambassador and brand image have a positive and significant effect on purchase intention. The correlation coefficient (R) was 0.448, while the coefficient of determination (R²) was 0.201, indicating that 20.1% of the variation in purchase intention is explained by brand ambassador and brand image, with the remaining 79.9% influenced by other factors. The t-test results show that brand ambassador (t = 4.937, sig. = 0.000) and brand image (t = 9.603, sig. = 0.000) both significantly affect purchase intention. The F-test (F = 71.719 > 3.18, sig. = 0.000) further confirms their simultaneous influence.